PENGARUH TEMPERATUR TUANG TERHADAP POROSITAS, STUKTUR MIKRO DAN KEKERASAN DARI ALUMUNIUM RONGSOK BALING-BALING KAPAL MENGGUNAKAN PENGECORAN EVAPORATIF - Jumalik, Jumalik; Siswanto, Rudi (JTAM ROTARY, 2022)
Aluminum and its alloys are the second largest metal material used after steel. Aluminum applications and alloys are very diverse, ranging from buildings, vehicle bodies, engine components, components to ships, to applications on aircraft. The strength and hardness of aluminum alloys are high, one application of aluminum as a component on a ship is as a material for making propellers on traditional fishing boats, more specifically aluminum alloy. Used aluminum can be obtained from the remnants of the industry making aluminum doors, windows and frames, making aluminum racks and storefronts, and other products with aluminum profile as the main material. many of them use aluminum alloy scrap as their main casting material to reduce their production costs. Evaporative or casting casting using Styrofoam or lost foam casting patterns is casting using a pattern of materials that can evaporate when exposed to molten metal heat. Casting uses a temperature of 650°C, 700°C, 750°C, 800°C. The results of casting temperature can affect porosity, microstructure, and hardness.